Membangun Kesadaran Bersama untuk Pembangunan Desa yang Berkelanjutan di Kabupaten Bengkalis - Taryono Taryono; Yelly Zamaya; Misdawita Misdawita; Cut Endang Kurniasih (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
This community engagement aims to enhance understanding of sustainable rural development in Bengkalis Regency through socialization in public meetings and FGDs. The socialization covers the 18 goals of Rural SDGs to provide an understanding of their relevance to local conditions. FGDs are used to explore challenges, opportunities, and formulate action plans. As a result, participants become more aware of the importance of responding to climate change and sustainable practices. Findings indicate commitment and progress in sustainable rural development. Thus, this engagement enhances understanding and involvement of stakeholders in achieving sustainable rural development goals in Bengkalis